Coal Loading and Unloading Safety Management on MV. Manalagi Samba - Jacobo, Esau Gallardo; Zapata, Carlos Romero (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2025)
Sea transportation is influenced by several factors such as the availability of supporting facilities or infrastructure and is also influenced by very good management. The support of equipment such as cranes and cranes used in the loading and unloading process has been thoroughly checked and functions properly so as not to cause risks to workers or the surrounding environment, fading each type of goods giving a warning sign if there are goods that are dangerous or require special treatment during the handling process. The study was conducted using a descriptive qualitative approach, which aims to understand various phenomena in depth through the perspective of participants in a natural context. The results of this study are: 1) Optimization of the implementation of loading and unloading at MV. Manalagi Samba including efficient schedule management, utilization of modern technology, increasing workforce competence, periodic equipment maintenance, evaluation of operational procedures, increasing communication between parties; and 2) Implementation of safety management in the implementation of loading and unloading at MV. Manalagi Samba including risk identification and assessment, preparation of Standard Operating Procedures (SOP), safety training and counseling, supervision and monitoring of the process, use of safe and proper equipment, effective communication, implementation of an incident reporting system, increasing awareness of safety culture.